2021
DOI: 10.3390/atmos12040442
|View full text |Cite
|
Sign up to set email alerts
|

What Are the Effects of Meteorological Factors on Exacerbations of Chronic Obstructive Pulmonary Disease?

Abstract: Chronic obstructive pulmonary disease (COPD) is one of the greatest global public health challenges. Acute exacerbations of COPD lead to the accelerated deterioration of lung function, reduced quality of life, a higher number of hospitalizations, and increased mortality. The factor causing the exacerbation is usually an infectious agent, but the impact of environmental factors is being studied more thoroughly. Among them, meteorological factors are the least examined. Multiple studies have shown that lower tem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 77 publications
1
5
0
Order By: Relevance
“…Our analysis demonstrated that extreme low temperatures and dew points, light wind speeds, high precipitation, and extreme high atmospheric pressure were risk factors for a higher number of COPD-related emergency visits. In agreement with our results, a literature review clearly showed that lower temperatures had a significant negative effect on patients with COPD [ 25 ]. A study from Poland reported significant negative correlations between the average temperature (r = −0.577), minimum temperature (r = −0.526), and dew point (r = −0.589) and an increased number of COPD-related ED visits with a significance level of p < 0.01 [ 26 ].…”
Section: Discussionsupporting
confidence: 93%
“…Our analysis demonstrated that extreme low temperatures and dew points, light wind speeds, high precipitation, and extreme high atmospheric pressure were risk factors for a higher number of COPD-related emergency visits. In agreement with our results, a literature review clearly showed that lower temperatures had a significant negative effect on patients with COPD [ 25 ]. A study from Poland reported significant negative correlations between the average temperature (r = −0.577), minimum temperature (r = −0.526), and dew point (r = −0.589) and an increased number of COPD-related ED visits with a significance level of p < 0.01 [ 26 ].…”
Section: Discussionsupporting
confidence: 93%
“…One of the important characteristics of obstructive respiratory diseases is their chronic course with a high frequency of exacerbations [1,5,34,35]. Accordingly, a significant part of the A group in our sample consisted of long-term patients in whom exacerbations of the underlying disease occurred in more than 50% of cases.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, we chose a 7-day lag period for this study. In addition, temperature and relative humidity have previously been shown to be associated with the AECOPD 17 , 18 , 27 . Taken together, the formula for the multiple pollutants model was specified as: where E(Yt) is the expected daily count of AECOPD cases on day t ; β is the intercept; and is the effect estimate of PM 2.5 p days before the onset day of AECOPD.…”
Section: Methodsmentioning
confidence: 99%
“…Recent epidemiological studies have indicated a positive association between low-level PM 2.5 exposure and the risk of AECOPD 12 15 . Some studies have also suggested that extreme meteorological conditions are associated with the occurrence of AECOPD 16 18 . However, few studies have explored the effect of high-level PM 2.5 and its interaction with meteorological factors on the development of AECOPD.…”
Section: Introductionmentioning
confidence: 99%